Clinical implications of Squat Jump and Countermovement Jump among young females of United Arab Emirates : Comparative Biomechanical Analysis - Tasnim Yahia Saad Salama; Maryam Abdelkawi Harb Abdelkawi Ali; Praveen Kumar Kandakurti; Meruna Bose; Ramprasad Muthukrishnan; Animesh Hazari (Central European Journal of Sport Sciences and Medicine, 2024)
Background: The countermovement jump (CMJ) and the squat jump (SJ) are two vertical jump (VJ) tests widely used to evaluate lower limb muscle strength and power, respectively. Biomechanical analysis of SJ and CMJ could help to predict the strength associated musculoskeletal clinical disorder which is most commonly seen among females such as patellofemoral pain syndrome, osteoarthritis etc. Therefore, the purpose of the study was to conduct and compare the biomechanical analysis of squat and countermovement jump using advanced motion analysis system and compare the changes among sedentary and active young females of the United Arab Emirates. Methodology: The experimental study was conducted at the Thumbay Physical Therapy and Rehabilitation Hospital, Gulf Medical University, Ajman, UAE. A total of 60 sedentary females, and 60 active females within age group 18-30 years were recruited under the convenience sampling method. The participants were randomly divided into two subgroups of 30 each for SJ and CMJ jump analysis respectively for sedentary and active group. Results: There was a statistically significant difference between the CMJ and SJ among the young females in UAE population (p < 0.05). The outcome variables such as jump height, and lower limb joint force were significantly reduced for SJ and CMJ in the sedentary group compared to active group. Majority of the variables showed moderate to severe effect size. Conclusion: Based on the study findings, it could be suggested that the “Sedentary Group” in the present study had poor muscle strength and ability to sustain the stress on the lower limb joints as also shown with lower mean total work. Since we have conducted the study on healthy non-athletes’ young females, the data could be used for further clinical correlation and comparison for lower limb muscle strength and power.